Liquiritin Attenuates Diabetic Nephropathy in Type 2 Diabetic Male Rats Irrespective of Antihyperglycemic Effect - Raad Saad Luty; Adeeb Ahmed Al-Zubaidy; Arif Sami Malik (Iraqi Journal of Pharmaceutical Sciences, 2025)
Diabetic nephropathy represents one of the common and serious complications of diabetes mellitus and it’s a leading cause of renal failure. Liquiritin is one of the main flavonoids found in Glycyrrhiza glabra that has been shown to have several pharmacological effects, such as the antioxidant, anti-inflammatory, anti-tumor, cardiovascular protection, hepatoprotection, and attenuation of rheumatoid arthritis in experimental animals. The present study investigated the protective effect of liquiritin against diabetic nephropathy in high fat diet and streptozotocin (STZ) induced diabetes mellitus in male rats.In the present study, the type 2 diabetes model was induced by feeding the animals with the high fat diet for four weeks, after that the animals were fasted overnight and injected with a single intraperitoneal dose of STZ 30 mg/kg. Liquiritin was administered daily at a dose of 40 mg/kg for 15 weeks. At the end of the experimental period, blood glucose level, glycated hemoglobin A1 (HbA1c), lipid profile markers, serum renal function parameters, renal index were assed, levels of inflammatory and oxidative markers namely interleukin-1beta (IL-1β), interleukin -6 (IL-6), tumor necrosis factor-alpha (TNF- α), and transforming growth factor-beta (TGF-β1), glutathione (GSH), and malondialdehyde (MDA) were determined in the renal homogenate, and the histopathological examination was performed by the use of hematoxylin and eosin staining, where the histopathological changes in kidney tissues were semi-quantitatively calculated according to a renal pathology scoring system.The diabetic control group showed a significant increase in the glycemic control parameters, and renal function parameters, and showed significant histopathological changes compared with the normal control group. The results revealed that liquiritin significantly improves histopathological changes while doesn’t affect the glycemic control parameters with a reduction in the inflammatory markers and oxidative stress in the renal homogenate.Liquiritin has an ameliorating effect against DN and it can significantly decrease most of the histopathological changes, and oxidative, and inflammatory markers.